Some Patterns in Center-State Fiscal Transfers in India: An Illustrative Analysis - Nirvikar Singh; Garima Vasishtha (University of California, Economics Department, 2004)
India's federal system is distinguished by tax and expenditure assignments that result in large vertical fiscal imbalances, and consequent transfers from the central government to the state governments. Several channels are used for these transfers: the Finance Commission, the Planning Commission, and central government ministries. We use panel data on center-state transfers to examine how the economic and political importance of the states influences the level and the composition of per capita transfers to the states, as well as differences in temporal patterns of Planning Commission and Finance Commission transfers. We find evidence that states with indications of greater bargaining power seem to receive larger per capita transfers, and that there is greater temporal variation in Planning Commission transfers.
Keywords: 330